Indonesia Economic Quarterly, September 2018 : Urbanization for All - World Bank (World Bank, Washington, DC, 2018)
Real GDP grew 5.3 percent in the second quarter of 2018 from the previous year, as domestic demand strengthened. Private and government consumption accelerated thanks to higher subsidy and personnelspending, a pick-up in credit growth, higher agricultural incomes, and stable inflation. Strong job markets also helped: the employment rate reached a two-decade high of 65.7 percent in February, with the unemployment rate falling to 5.1 percent. Growth of machinery and equipment investment remained robust, but overall gross fixed capital formation (GFCF) slowed because investments in structures and buildings (three-quarters of GFCF) moderated, partly due to fewer working days. Despite escalating protectionism, both exports and imports grew over the quarter. Because import volumes grew nearly twice as fast as exports, net exports contracted, weighing on overall economic growth.